Peningkatan kualitas produk olahan susu dengan penyimpanan hasil produksi yang efektif - Rumijati, Aniek; Asfiah, Nurul; Rima Fiandari, Yulist (University of Islam Malang, 2021)
The development of Café Sawah as Village Tourism in Pujon Kidul is very important because it has an impact on improving the community's economy. So far, various dairy products by MSEs that are fostered by ‘Aisyiyah are sticks and crackers as typical souvenirs from Pujon Kidul Tourism. The souvenirs are still not packaged attractively. Product packaging is an effective marketing strategy in managing the end of production, until it is accepted by the end consumers. As a tourist area that is crowded with visitors, good and effective processing of souvenirs is a solution that can be offered to visitors as souvenirs. The purpose of this community service is to improve good packaging, elegant design, easy to carry and able to maintain the quality of the product during the trip. This community service methods are observation, audience and active participation, in order to increase the value of souvenir products with more attractive packaging, safe and comfortable, with local wisdom. The result of this community service is packaging that has an attractive design, an elegant impression of the product, improving of the product values, and so, it becomes a promotional medium when it is brought to a new place as a souvenir, and then, it will subsequently have impact on increasing the welfare of the surrounding community, especially MSEs fostered by ‘Aisyiyah.